Configuration Management Maturity in Scientific Facilities. (12th December 2013) - Niknam, Masoud; Bonnal, Pierre; Ovtcharova, Jivka
Since the effectiveness of the development and operation of scientific facilities (especially those presenting specific hazards, such as ionizing radiations) relies heavily on state of the art practices, such as systems engineering and product lifecycle management, configuration management (CM) is becoming a key management process. However, while some maturity models exist to assess the degree of the implementation and effectiveness of many management processes, such as project management or systems engineering, there is no specific framework available to assess the degree of maturity of an organization towards CM. This paper focuses on revealing the important maturity dimensions and levels for CM as a means towards developing a CM maturity model.